Optimal control of HIV treatment and immunotherapy combination with state and control delays. (4th December 2019) - Silva, Cristiana J.; Maurer, Helmut
Summary: In this paper, we propose and analyze an optimal control problem where human immunodeficiency virus treatment and immunotherapy are described by two control functions that are subject to time delays representing pharmacological and absorption delays, respectively. The goal is to propose effective optimal control solutions for the combination of human immunodeficiency virus treatment and immunotherapy, ensuring a functional behavior of the immune system. The incubation period is mathematically represented by a time delay in the virus load, and the local asymptotic and Hopf bifurcation analysis of the CTL‐equilibrium point of the uncontrolled delayed system is studied. We obtain optimal controls of bang‐singular type both for the nondelayed and delayed optimal control problem with and without state constraints. We study boundary arcs of state constraints and junction properties of the control and adjoint variables at entry and exit points of boundary arcs. Moreover, we derive an explicit formula of the multiplier associated with the state constraint.